Immune responses and resistance of white shrimp (Litopenaeus vannamei) fed Probiotic Bacillus sp NP5 and prebiotic honey against White Spot Syndrome Virus infection - Widanarni, Widanarni; Rahmi, Dewi; Gustilatov, Muhamad; Sukenda, Sukenda; Utami, Diah Ayu Satyari (Jurnal Akuakultur Indonesia, 2020)
ABSTRACT White spot disease caused by White Spot Syndrome Virus (WSSV) is the most serious viral disease and has a major impact on the decline in production of white shrimp farm. Improving the immune response through the application of prebiotic, probiotic and synbiotic is expected to be one of the environmentally friendly alternatives to prevent the disease. This study aimed to evaluate the effect of administrating Baccillus sp. NP5 probiotic, honey prebiotic and a combination both (synbiotic) in enhancing immune response and resistence of white shrimp to WSSV infection. This study consisted of five treatments and three replications, namely positive control (feeding without probiotics, prebiotics, and synbiotics then challenged with WSSV), negative control (feeding without probiotics, prebiotics, synbiotics, then injected with PBS), pro (feeding with the addition of Bacillus sp. NP5 probiotics then challenged against WSSV), pre (feeding with the addition of honey prebiotics then challenged against WSSV), and sin (feeding with the addition of synbiotics then challenged against WSSV). White shrimp with an average weight of 1.8±0.06 gram/shrimp were reared at a density of 15 shrimps per aquarium (60 cm x 30 cm x 30 cm and water height of 20 cm) for eight weeks, then challenge against WSSV at lethal dose (LD50) dose as much as 0.1 ml per shrimp. The results showed that the immune response and resistence of white shrimp after treatments of probiotics, prebiotics, and synbiotics were better than those in controls with the optimal found in prebiotics treatment. Keywords: Bacillus sp. NP5, honey, immune response, white shrimp, WSSV ABSTRAK White spot disease yang disebabkan oleh infeksi white spot syndrome virus (WSSV) merupakan penyakit viral paling serius dan berdampak besar terhadap penurunan produksi budidaya udang vaname. Perbaikan respons imun melalui aplikasi probiotik, prebiotik dan sinbiotik dapat menjadi salah satu alternatif ramah lingkungan untuk pencegahan serangan penyakit tersebut. Penelitian ini bertujuan untuk mengevaluasi pengaruh pemberian probiotik Bacillus sp. NP5, prebiotik madu dan gabungan keduanya (sinbiotik) dalam meningkatkan respons imun dan resistansi udang vaname terhadap infeksi WSSV. Penelitian ini terdiri dari lima perlakuan dan tiga ulangan yaitu kontrol positif (pemberian pakan tanpa probiotik, prebiotik, dan sinbiotik kemudian diuji tantang dengan WSSV), kontrol negatif (pemberian pakan tanpa probiotik, prebiotik, dan sinbiotik kemudian diinjeksi PBS), pro (pemberian pakan dengan penambahan probiotik Bacillus sp. NP5 kemudian diuji tantang dengan WSSV), pre (pemberian pakan dengan penambahan prebiotik madu kemudian diuji tantang WSSV), dan sin (pemberian pakan dengan penambahan sinbiotik kemudian diuji tantang dengan WSSV). Udang vaname dengan bobot rata-rata 1.8±0.06 gram/ekor dipelihara dengan kepadatan 15 ekor per akuarium (60 cm x 30 cm x 30 cm) selama delapan minggu, kemudian diuji tantang dengan WSSV sebanyak 0.1 ml per ekor pada dosis LD50. Hasil penelitian menunjukkan bahwa respons imun dan resistansi udang vaname setelah pemberian probiotik, prebiotik dan sinbiotik lebih baik (P<0.05) dibandingkan kontrol dengan hasil optimal pada perlakuan prebiotik. Kata kunci: Bacillus sp. NP5, madu, respons imun, udang vaname, WSSV.